Versatile mechanisms of 2-substituted benzimidazoles in targeted cancer therapy - Heba A. Ibrahim; Hanan M. Refaat (SpringerOpen, 2020)
Abstract Background The aim of this review is to provide an overview on diverse anticancer activities of 2-substituted benzimidazole derivatives. Main body This review provides a correlation between the various mechanisms of action of benzimidazoles as anticancer and the substitution pattern around the nucleus. Conclusion The linker group and substitution at N-1, C-2, C-5, and C-6 positions have been found to be the most contributory factors for anticancer activity. This will help in the further design to afford more selective, potent, and multi-target anticancer of 2-substituted benzimidazole-based compounds.